2023
DOI: 10.3390/plants12101932
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis of the Late-Acting Self-Incompatibility Associated with RNase T2 Family in Camellia oleifera

Abstract: The Camellia oil tree (Camellia oleifera Abel.) is an important nonwood forest species in China, and the majority of its cultivars are late-acting self-incompatibility (LSI) types. Although several studies have examined the mechanism of LSI, the process is quite complicated and unclear. In this study, pollen tube growth and fruit setting of two Camellia oil tree cultivars Huashuo (HS) and Huajin (HJ) were investigated after non and self-pollination, and transcriptomic analysis of the ovaries was performed 48 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 78 publications
(97 reference statements)
0
1
0
Order By: Relevance
“…Compared with GSI and SSI, LSI is poorly understood. Transcriptomic analysis of pistils has revealed that LSI is closely associated with Ca 2+ signaling, plant hormone signal transduction, ATP-binding cassette (ABC) transporters, the mitogen-activated protein kinase (MAPK) signaling pathway, reactive oxygen species (ROS) metabolism, PCD-related genes, ubiquitin-mediated proteolysis, and the phosphatidylinositol signaling system [ 36 , 37 , 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…Compared with GSI and SSI, LSI is poorly understood. Transcriptomic analysis of pistils has revealed that LSI is closely associated with Ca 2+ signaling, plant hormone signal transduction, ATP-binding cassette (ABC) transporters, the mitogen-activated protein kinase (MAPK) signaling pathway, reactive oxygen species (ROS) metabolism, PCD-related genes, ubiquitin-mediated proteolysis, and the phosphatidylinositol signaling system [ 36 , 37 , 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%